Hubungan Antara Disiplin Kerja, Motivasi Dan Pemberdayaan Terhadap Kinerja Karyawan Pada Hotel Ciputra Jakarta: Studi Kuantitatif Pada Program Studi Manajemen Universitas Muhammadiyah Prof. DR. HAMKA (UHAMKA). - Desi Chandra (UHAMKA Graduate School Thesis Abstract Collection, 2016)
The goal of research conducted to determine whether there is relationship of discipline, Motivation and fasility performance to Hotel Ciputra employees . Used as research method and the respondents are Hotel Ciputra employees. The type at the research is explanatory research, as this study describes the relationship of discipline, motivation and Empowerment performance to the employees . The data was collected through questionnaires. Multiple regression analysis is used to analyse the data. The result shows that discipline, motivation and Empowerment relationship employees , with the contribution of determination (R2) of 0,594 or 59,4%, while for 0,406 or equal to 40,6 % was explained by the variable other than the concept of research and the resulting regression equation is Y = 4,185 + 0,249X1 + 0,159X2 +0,335X3, F-test results obtained for 13,631 > 2.92 with a significance 0,000 < 0,05, means variables of discipline, Motivation and Empowerment relationship simultaneously employees significantly. The result shows that the variables of Empowerment the has more dominant effect on the performance in the employees at Hotel Ciputra in the amount of 0,335, while the relationship of discipline variable is 0,249 and 0,159 for the relationship of motivation variable. From the results of the research also concluded that the performance on employees at Hotel Ciputra will increase more if the discipline, motivation and Empowerment are latter. Discipline can be improved by giving employees the opportunity to obtain higher education and better training quality, motivation can be done by encouraging employees to do innovative work, giving appreciation to outstanding employees and together make plans and set goals for company achievement.